Scan, Pay, and Eat: Digitalization Service to Enhance Customer’s Experience at Goemerot Restaurant - Agustina Riski Gusti Ayu (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
The Industrial Revolution 5.0 is encouraging businesses in the culinary industry worldwide to transform from traditional, human-centric restaurants into smart restaurants that apply technological innovations to their services. These smart restaurants are expected to enhance the digital experience for customers, thereby increasing service efficiency, speeding up table turnover, minimizing errors, and improving data accuracy. This research aims to identify the technological innovations implemented by Goemerot Restaurant to improve customer experience. A qualitative approach was used for the research method. The data obtained is both primary and secondary. Primary data was obtained through direct observation and interviews using the purposive sampling method. Interviews were conducted with supervisors, waiters, and customers. Secondary data was obtained through a literature study. The data is presented using the data triangulation method with a thematic approach. The research results show that Goemerot Restaurant has implemented the following innovations: self-ordering via QR code, digital payment, integration with online delivery services, and wireless call buttons. This restaurant's customers have not fully accepted the transformation that began in mid-2025, so waiter assistance is needed if customers have trouble adapting to the digitalization of these services.